Creating Architectural Models from Images - Liebowitz, David; Criminisi, Antonio; Zisserman, Andrew (Proc. EuroGraphics (EG), 1999)
We present methods for creating 3D graphical models of scenes from a limited numbers of images, i.e. one or two, in situations where no scene co-ordinate measurements are available. The methods employ constraints available from geometric relationships that are common in architectural scenes such as parallelism and orthogonality together with constraints available from the camera. In particular, by using the circular points of a plane simple, linear algorithms are given for computing plane rectification, plane orientation and camera calibration from a single image. Examples of image based 3D modelling are given for both single images and image pairs.